The Crop Load Affects Brown Rot Progression in Fruit Orchards: High Fruit Densities Facilitate Fruit Exposure to Spores but Reduce the Infection Rate by Decreasing Fruit Growth and Cuticle Cracking - Bellingeri, Michele; Quilot-Turion, Benedicte; Oliveira Lino, Leandro; Bevacqua, Daniele (Frontiers in Ecology and Evolution, 2018)
Brown rot, triggered by Monilinia spp., causes significant economic losses in fruit crop and it is mainly controlled by chemicals with inherent environmental costs. Controlling brown rot spreading by diminishing fruit susceptibility to the disease, via sustainable cultural practices, is a promising approach. In a two years experiment (2014-2015) on a peach (Prunus persica) orchard, we controlled fruit growth rates by varying the fruit load. Fruit thinning practices enhanced the fruit growth and laboratory analyses showed that, in both 2014 and 2015 samples, fast growing fruits were more susceptible to infection when in contact with conidia suspension of Monilinia laxa. In the field, brown rot infection took place in 2014 and not in 2015. In 2014, trees subject to moderate thinning intensities had the highest brown rot incidence. We argue that this is due to the fact that, for null thinning, slow growing fruits are less susceptible to the infection while, for intense thinning, even if faster growing fruits are more susceptible to infection, the lower fruits density reduces per-contact probability of infection. We compared meteorological data of 2014 and 2015 and we argue that brown rot did not spread in 2015 due to an absence of favorable conditions, summarized as the number of rainy days with mean temperature between 22 and 26 °C , in the period of fruit susceptibility.